External and internal training load relationships in soccer players - Alemdaroglu, U. (Journal of Human Sport & Exercise, 2021)
The aim of the present study was to examine the relationships between internal training loads (TL) (Polar (PLR), Edwards (EDW) Training-Impulse (TRIMP) session RPE (s-RPE) external TL (Total distance (TD), covered distance in five different zone, number of acceleration (ACC) and deceleration actions (DEC) in professional soccer players. Twenty male professional soccer players (age = 27.6 years; height = 177.6 ± 7.1 cm; body mass = 69 ± 8.3 kg) from a professional soccer team voluntarily participated in the study. The correlations between the values were examined individually for each athlete by Pearson correlation test. According to the results of this study showed that there were very large and nearly perfect relations between s-RPE and both HR-based methods (EDW and PLR TRIMP) (respectively, r = .51 - .91; r = .44 -. 90). Additionally, from moderate to large correlations were observed between internal TL methods and external TL methods (walking, number of ACC-DEC actions) (between r = .56 - .82). Moreover, the relations between internal load and external load parameters were weakened in high-speed zones. According to the results of the current study, meanwhile s-RPE may be evaluated in practice as a useful and inexpensive for monitoring the internal TL method, the number of ACC and DEC actions could be appropriate for external TL.